Magnetic resonance imaging findings in brain resulting from high-voltage electrical shock injury of the scalp - Chandrasekhar, Dileep P; Noone, Mohan L; Babu, S P Harish; Bose, V T Chandra (Indian Journal of Radiology and Imaging, 2018)
We report a case of high-voltage electrical injury to scalp, focusing on the magnetic resonance imaging (MRI) findings in brain. A 51-year-old male suffered burns to the right side of scalp and loss of consciousness following electric shock. Brain abnormalities were detected on MRI taken 4 days after the insult. Right parietal lobe neuroparenchyma beneath the scalp burn defect demonstrated homogeneous hypointensity on T1-weighted MR images, while T2-weighted images depicted hyperintensity mainly in white matter forming finger-like projections. Follow-up MRI showed that the abnormality had disappeared, indicating that the cerebral edema was reversible.
Keywords: Brain imaging; electrical burn; electrical injury